Therapists Make the Switch to Telepsychology to Safely Continue Treating Their Patients During the COVID-19 Pandemic. Virtual Reality Telepsychology May Be Next - Sampaio, Mariana; Navarro Haro, Maria Vicenta; De Sousa, Bruno; Vieira Melo, Wilson; Hoffman, Hunter G. (Frontiers in Virtual Reality, 2021)
Before COVID-19, most therapists had concerns about telepsychology, and only treated patients in person. During the COVID-19 lockdown, patients still needed therapy, but in-person therapy sessions became unsafe. The current study measured how many therapists are using online therapy before vs. during COVID-19, how much training they have received, and their knowledge about legal restrictions on using telepsychology. A sample of 768 U.S.A. mental health professionals completed a 29-item online survey. Results show that before COVID-19, most therapists only saw their patients in person (e.g., at the therapists office), but during the COVID-19 pandemic, nearly all therapists used a wide range of telecommunication technologies to communicate with their quarantined patients, including texting, telephones, video conferences, and even virtual reality. According to within-subject related samples comparisons, 39% of survey respondents used telepsychology before COVID-19, vs. 98% during COVID-19 (χ2 = 450.02, p < .001). Therapists reported high treatment effectiveness using telepsychology (7.45 on 0-10 scale). However, overall, on a 0-10 scale, therapists reported a significant increase in feeling burned out during the COVID-19 pandemic, Mean = 3.93 (SD =1.93) before vs. 6.22 (SD = 2.27) during the pandemic (Z = -18.57, p < .001). Although the APA ethics guidelines encourage therapists to use telepsychology with their patients during the crisis, gaps in respondents’ knowledge identify a need for increased specialized training and education. Although the current study showed that virtual reality is rarely used by the therapists surveyed, virtual reality is a promising new telepsychology technology. Billions of dollars are currently being invested in mass producing immersive virtual reality systems. In the future, as networked immersive Virtual Reality becomes more widely available, therapists and patients in physically different locations will be able to “meet” in a shared computer-generated world designed for therapy sessions, potentially including group sessions. Telepsychology and virtual reality have the potential to be increasingly valuable tools to help therapists mitigate the consequences of COVID-19. Research, development and training is recommended.